Relasi Filsafat dan Agama (Perspektif Islam) - Hidayatullah, Syarif (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2007)
There are two main issues in this article, namely: firstly, isabout major distinction of the concept of knowledge truth inphilosophy and religion, and, secondly, is about relation betweenphilosophy and religion. In the first issue, it is mentioned thatalthough philosophy and religion are similarly in creation normstruth and false, but the both are differently in determining itscriteria. Religion, on the side, determines these criteria based onwahyu (revelation), so it results the true or absolute truth. On otherside, philosophy determines these criteria based on aql (reason), soit results the speculative or relative truth. While in the secondissue, the article explains that to seek the truth of knowledge or thetrue knowledge, so philosophy can used really as a good tool toexplain and support religion position. Whereas religion can used asa source to inspirited fervent and true philosophical thinking. Pointof intersection of the both is its position in the same matter,namely: “the Ultimate Reality”. However, distinction of the both isnot site in that matter of intersection, but it site in the way ormethod to research it.